2005
DOI: 10.1038/labinvest.3700300
|View full text |Cite
|
Sign up to set email alerts
|

Human bronchial fibroblasts exhibit a mesenchymal stem cell phenotype and multilineage differentiating potentialities

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells able to differentiate along different pathways including chondrogenic, osteogenic and adipogenic lineages. MSCs with a fibroblast-like morphology have been identified in human fetal lung. However, their frequency and characterization in human adult lung have not been yet evaluated. Therefore, we analyzed the mesenchymal phenotype and differentiation ability of cultured human adult bronchial fibroblast-like cells (Br) in comparison with those of mesenchymal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
174
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(188 citation statements)
references
References 31 publications
6
174
0
8
Order By: Relevance
“…Over the last several years MSCs have been derived from a variety of other tissues of adult [5][6][7] or fetal origin [8,9]. Interestingly, these MSCs have also been shown to have a wider differentiation capability in vitro and in vivo than previously appreciated, at least in some experimental models, [10][11][12] and thus have attracted attention as very desirable cells for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years MSCs have been derived from a variety of other tissues of adult [5][6][7] or fetal origin [8,9]. Interestingly, these MSCs have also been shown to have a wider differentiation capability in vitro and in vivo than previously appreciated, at least in some experimental models, [10][11][12] and thus have attracted attention as very desirable cells for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few markers have been developed and proved suitable for the isolation of MSCs from primary tissues. Markers that meet established criteria for their positive selection include STRO-1, CD73, CD105 and CD271, whereas CD45 and CD235 (glycophorin A) are used for the negative selection of MSCs [6,[18][19][20][21][22]. The International Society for Cellular Therapy (ISCT) proposed three minimal criteria for defining MSCs: 1) these cell population must be plastic-adherent when maintained in standard culture conditions using tissue culture flasks; 2) ≥95% of the MSCs population must express CD105, CD73 and CD90, as measured by flow cytometry and lack expression (≤52% positive) of CD45, CD34, CD14 or CD11b, CD79a or CD19 and HLA class II; and 3) MSCs must be able to differentiate to osteoblasts, adipocytes and chondroblasts under standard in vitro differentiating conditions [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Bone-marrow derived MSCs represent a mixture of different MSC populations and had been shown to be true for MSC from lung tissue [12]. Sabatini et al [13] showed that a plastic adherent cell population exists in human lungs isolated via BAL [14], or via tissue digestion [15]. These cells are either long-lived or not mutually exclusive and have the capacity for renewal.…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%